2017
DOI: 10.1016/j.tig.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Factor Mutations in Myelodysplasias: Insights from Spliceosome Structures

Abstract: Somatic mutations of pre-mRNA splicing factors recur among patients with myelodysplastic syndromes (MDS) and related malignancies. Although these MDS-relevant mutations alter splicing of a subset of transcripts, the mechanisms by which these single amino acid substitutions change gene expression remain controversial. New structures of spliceosome intermediates and associated protein complexes shed light on the molecular interactions mediated by “hotspots” of the SF3B1 and U2AF1 pre-mRNA splicing factors. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 116 publications
3
66
0
2
Order By: Relevance
“…This, along with studies that advance a more detailed mechanistic understanding of the splicing process[35, 62] at both the single-gene and genome-wide levels, are key to advancing SPLMs into the clinic. [63]…”
Section: Resultsmentioning
confidence: 99%
“…This, along with studies that advance a more detailed mechanistic understanding of the splicing process[35, 62] at both the single-gene and genome-wide levels, are key to advancing SPLMs into the clinic. [63]…”
Section: Resultsmentioning
confidence: 99%
“…Somatic mutations in SF3B1 are frequently found in MDS and chronic lymphocytic leukemia (CLL) patients [50,51]. Studies suggest that mutations in SF3B1 induce malignancy through aberrant transcription, altered pre-mRNA recognition and alternative splicing [50,52]. Similarly, mutations in PRPF8 have been identified in MDS and AML patients where decreased PRPF8 expression is associated with increased exon skipping [53], possibly due to a splicing proofreading defect [53].…”
Section: Ddx41 In Mrna Splicingmentioning
confidence: 99%
“…1 Previous reports have shown that U2AF65 might be a key regulator of gene expression and related signalling pathway. U2AF65 is encoded by U2AF2 gene, and previous studies have confirmed the central role of U2AF65 in splicing.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A series of U2AF mutations have been characterized to investigate the functions of U2AF as a splicing factor, and previous studies have revealed that the stoichiometry of U2AF is important for accurate 3′ ss selection. The function of U2AF65 in alternative splicing has been identified; however, the essential physiological role of U2AF65 remains poorly understood.…”
mentioning
confidence: 99%